Comparative inhibitory effect of prenylated coumarins, ferulenol and ferprenin, contained in the 'poisonous chemotype' of Ferula communis on mammal liver microsomal VKORC1 activity. (October 2015) - Louvet, Marie-Sophie; Gault, Gilbert; Lefebvre, Sébastien; Popowycz, Florence; Boulven, Manon; Besse, Stéphane; Benoit, Etienne; Lattard, Virginie; Grancher, Denis
Graphical abstract: Ferulenol, and to a lesser extent, ferprenin, are both inhibitors of VKORC1 enzymes in all animals exposed to Ferula communis, and thus are both responsible for 'ferulosis'. Highlights: Ferulenol and ferprenin inhibit VKORC1 in all animals exposed to Ferula communis . Ferulenol is a much more potent inhibitor of VKORC1 than ferprenin. Ferulenol, and to a lesser extent, ferprenin are thus responsible for 'ferulosis'. Cow might be more resistant to 'ferulosis' than other species. Abstract: Two distinguishable chemotypes of Ferula communis have been described: the 'nonpoisonous' chemotype, containing as main constituents the daucane esters; and the 'poisonous' chemotype containing prenylated coumarins, such as ferulenol and ferprenin. Ferulenol and ferprenin are 4-oxygenated molecules such as dicoumarol and warfarin, the first developed antivitamin K molecules. Antivitamin K molecules specifically inhibit VKORC1, an enzyme essential for recycling vitamin K. This latest is involved in the activation of clotting factors II, VII, IX, X. The inhibiting effect of ferulenol on VKORC1 was shown in rat, but not for species exposed to F. communis while in vivo studies suggest differences between animal susceptibility to ferulenol. The inhibiting effect of ferprenin on VKORC1 was never demonstrated. The aim of this study was to compare the inhibiting effect of both compounds on VKORC1 of different species exposed to F. communis . Vitamin K epoxide activity was evaluated for each species from liver microsomes and inhibiting effect of ferulenol and ferprenin was characterized. Ferulenol and ferprenin were shown to be able to inhibit VKORC1 from all analyzed species. Nevertheless, susceptibility to ferulenol and ferprenin presented differences between species, suggesting a different susceptibility to 'poisonous' chemotypes of F. communis .